Tratamiento periodístico de la información política en los medios de comunicación impreso, el correo y opinión de la ciudad de Machala, en el tercer trimestre del año 2011. - Cedillo Rodríguez, Hamilton Alexander (2015)
This research work has a purpose determine which journalistic treatment give printed media, mail and view of the city of Machala to political information during the third quarter of 2011, It was necessary to analyze the related news Central Government, National Assembly , Municipality of Machala, passing laws, demonstrations and events such as conferences or talks where the Mayor of Machala or Presidency which were published in the newspapers Post and Opinion relating in the months of July, August and September.